Eksplorasi Penelaran Spasial pada Konstruk Rotasi Mental dengan Media Google SketchUp - Akbar, Khairul (Jurnal Didaktika Pendidikan Dasar, 2021)
This study aimed to describe students’ spatial thinking in the mental rotation mental rotation construct before and after exploring Google SketchUp media. This study is a qualitative approach and case study methods. Each participants was selected by two students with high, medium, and low mathematical abilities respectively. The instruments were written tests of mental rotation construct and interview guidelines. The research procedures were: (1) students worked on pre-test ; (2) initial interview; (3) students explored rotations activities with Google SketchUp; (4) student worked on post-test; (5) final interview. Results of the pre-test and initial interviews showed that students struggled to employ spatial reasoning in mental rotation construct for the cube rotation in all directions. The results of the post-test and the final interview showed that these six students were able to employ spatial reasoning in mental rotation construct for all indicators. Thus it is concluded that the use of Google SketchUp media can change the way of thinking of mental rotation constructs of spatial thinking.